(untitled) (مجلة إحالات, 2026)
Since we are living under the shadow of Globalization, internet-based learning environments are the mainstream of education. Audio and video conferencing, online applications, wikis, and Open Online Educational Resources (OOER) in general are the tools used to create collaboration and interaction among students and teachers and form supportive instructional milieus. An avalanche of literature gives attention to the role of virtual collaboration in developing students’ and teachers’ skills and competencies. Yet, the acceptance of learning via such online environments is still problematic. In this regard, the present paper aims to measure students’ and teachers’ attitudes towards virtual collaboration. Online students’ questionnaires and teachers’ interviews were used as the main research tools. Results indicate that respondents acknowledge the usefulness of online learning formats, though many students have generated favourable reactions to face-to-face classes due to instructors’ and classmates’ physical presence. Results also reveal that teachers’ negative attitude is mainly linked to their lack of ICTs training and expertise. In this vein, some competencies need to be further developed, such as getting to deal with others and solving problems collectively without forgetting to reinforce teachers’ information literacy skills to help them manage online learning environments and groups.